Designing Simple Lipidated Lysines: Bifurcation Imparts Selective Antibacterial Activity. (12th October 2016) - Ghosh, Chandradhish; Konai, Mohini Mohan; Sarkar, Paramita; Samaddar, Sandip; Haldar, Jayanta
Abstract: In the global effort to thwart antimicrobial resistance, lipopeptides are an important class of antimicrobial agents, especially against Gram‐negative infections. In an attempt to circumvent their synthetic complexities, we designed simple membrane‐active agents involving only one amino acid and two lipid tails. Herein we show that the use of two short lipid tails instead of a single long one significantly increases selective antibacterial activity. This study yielded several selective antibacterial compounds, and investigations into the properties of this compound class were conducted with the most active compound. Fluorescence spectroscopic studies revealed the capacity of the representative compound to cause depolarization and permeabilization of bacterial cell membranes. This membrane‐active nature of the compound imparts superior activity against persister cells, biofilms, and planktonic cells. Topical application of the compound decreased bacterial burden in mice inflicted with burn‐infections caused by Acinetobacter baumannii . We anticipate that the design principles described herein will direct the development of several antimicrobial agents of clinical importance. Abstract : How simple but selective antibacterial membrane‐active agents can be designed is presented herein. Bifurcation of long alkyl chains into two short chains leads to selective antibacterial activity. A representative bifurcated compound exhibits broad‐spectrum bactericidal activity and disrupts biofilms. It also treats burn wounds in mice infected with Acinetobacter baumannii . This principle could be applied to further designs of membrane‐active agents.